State of the World's Cities 2012/2013 Prosperity of cities - UN HABITAT (New York Earthscan, 2013)
The City is the Home of Prosperity. It is the place where human beings find satisfaction of basic needs and access to essential public goods. The city is also where ambitions, aspirations and other material and immaterial aspects of life are realized, providing contentment and happiness. It is a locus at which the prospects of prosperity and individual and collective well-being can be increased.
Includes bibliographies
Keywords: Urbanization